Promoting Diverse Youth's Career Development through Informal Science Learning: The Role of Inclusivity and Belonging. - Zhao, Mengya; Mathews, Channing J.; Mulvey, Kelly Lynn; Hartstone-Rose, Adam; McGuire, Luke; Hoffman, Adam J.; Winterbottom, Mark; Joy, Angelina; Law, Fidelia; Balkwill, Frances; Burns, Karen P.; Butler, Laurence; et al. (Journal of Youth & Adolescence, 2023)
Little research has examined the associations between perceived inclusivity within informal science learning sites, youth program belonging and perceptions of program career preparation. This study explored relations between these factors at three timepoints (T1 = start of program, T2 = 3 months and T3 = 12 months after start). Participants were a diverse sample of 209 adolescents participating in STEM youth programs within informal science learning sites situated in the United States and United Kingdom (70% females: M = 15.27, SD = 1.60), with 53.1% British and 64.1% non-White. Path analysis revealed that only perceptions of inclusivity for own social identity group (i.e., gender, ethnicity) at T1 were associated with T2 STEM youth program belonging. There was a significant indirect effect of T1 perceptions of inclusivity for one's own social identity groups on T3 perceptions of program career preparation via T2 program belonging. This study highlights that, over time, perceptions of inclusivity around youth's own social identity groups (i.e., gender and ethnicity/culture) are related to a sense of youth program belonging, which in turn is later associated with perceptions of program career preparation.